The Influence of Climate, Atmospheric Pollution, and Natural Disasters on Cardiovascular Diseases and Diabetes Mellitus in Drylands: A Scoping Review - Rafaella Pessoa Moreira; Clara Beatriz Costa da Silva; Tainara Chagas de Sousa; Flávia Lavinnya Betsaida Félix Leitão; Huana Carolina Cândido Morais; Andressa Suelly Saturtino de Oliveira; Gonzalo Duarte-Clíments; Gonzalo Duarte-Clíments; María Begoña Sánchez Gómez; María Begoña Sánchez Gómez; Tahissa Frota Cavalcante; Alexandre Cunha Costa (Frontiers Media S.A., 2024)
ObjectivesIn the face of escalating global aridification, this study examines the complex relationship between climate variability, air pollution, natural disasters, and the prevalence of cardiovascular disease (CVD) and diabetes mellitus (DM) in arid regions.MethodsThe study conducted a scoping review of multiple databases using JBI guidelines and included 74 studies.ResultsThe results show that acute myocardial infarction (n = 20) and stroke (n = 13) are the primary CVDs affected by these factors, particularly affecting older adults (n = 34) and persons with hypertension (n = 3). Elevated air temperature and heat waves emerge as critical risk factors for CVD, exacerbating various cardiovascular mechanisms. Atmospheric pollutants and natural disasters increase this risk. Indirect effects of disasters amplify risk factors such as socioeconomic vulnerability (n = 4), inadequate medical care (n = 3), stress (n = 3), and poor diet (n = 2), increasing CVD and DM risk.ConclusionThe study underscores the need for nations to adhere to the Paris Agreement, advocating for reduced air pollutants, resilient environments, and collaborative, multidisciplinary research to develop targeted health interventions to mitigate the adverse effects of climate, pollution, and natural disasters.